(untitled) (The Agriculturists, 2014)
In the paper entitled Insecticidal Activity of Some Plant Extracts Against Trogoderma granarium (E.) published in The Agriculturists 11(1): 103-111 (June 2013), the authors should be read as Farooq Ahmad, Muhammad Sagheer, Ahmad Hammad, S. M. Mizanur Rahman and Mansoor-Ul-Hasan instead of Farooq Ahmad, Muhammad Sagheer, Ahmad Hammad, S. M. Mizanur Rahman and Masoor-Ul-Hasan. DOI: http://dx.doi.org/10.3329/agric.v11i2.17498 The Agriculturists 2013; 11(2) 114